2006
DOI: 10.1523/jneurosci.3424-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.7 Mutant A863P in Erythromelalgia: Effects of Altered Activation and Steady-State Inactivation on Excitability of Nociceptive Dorsal Root Ganglion Neurons

Abstract: Inherited erythromelalgia/erythermalgia (IEM) is a neuropathy characterized by pain and redness of the extremities that is triggered by warmth. IEM has been associated with missense mutations of the voltage-gated sodium channel Na v 1.7, which is preferentially expressed in most nociceptive dorsal root ganglia (DRGs) and sympathetic ganglion neurons. Several mutations occur in cytoplasmic linkers of Na v 1.7, with only two mutations in segment 4 (S4) and S6 of domain I. We report here a simplex case with an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 38 publications
12
122
1
Order By: Relevance
“…Previously described PEPD mutations have been shown to impair inactivation and have not been reported to affect activation or deactivation (Fertleman et al, 2006;Jarecki et al, 2008). In contrast, mutations linked to IEM have been observed to hyperpolarize activation and slow deactivation, either without an effect on inactivation (Cummins et al, 2004;Choi et al, 2006;Lampert et al, 2006;Sheets et al, 2007;Cheng et al, 2008) or coupled to a shift in inactivation voltage dependence, which was, nevertheless, complete (Dib-Hajj et al, 2005;Han et al, 2006;Harty et al, 2006). The shifts of voltage dependence of activation and fast inactivation for these PEPD and IEM mutants are illustrated in Figure 8.…”
Section: Discussionmentioning
confidence: 88%
“…Previously described PEPD mutations have been shown to impair inactivation and have not been reported to affect activation or deactivation (Fertleman et al, 2006;Jarecki et al, 2008). In contrast, mutations linked to IEM have been observed to hyperpolarize activation and slow deactivation, either without an effect on inactivation (Cummins et al, 2004;Choi et al, 2006;Lampert et al, 2006;Sheets et al, 2007;Cheng et al, 2008) or coupled to a shift in inactivation voltage dependence, which was, nevertheless, complete (Dib-Hajj et al, 2005;Han et al, 2006;Harty et al, 2006). The shifts of voltage dependence of activation and fast inactivation for these PEPD and IEM mutants are illustrated in Figure 8.…”
Section: Discussionmentioning
confidence: 88%
“…Among sodium channel isoforms, Na V 1.7 is of particular interest because of emerging evidence from genetic studies that correlate alterations in Na V 1.7 with human syndromes characterized by spontaneous pain (Yang et al, 2004;Choi et al, 2006;Fertleman et al, 2006). Mutations in the coding sequence of Na V 1.7 that result in channels that are electrically hyperexcitable produce a painful condition (Harty et al, 2006), and it has been shown that an increase in the number of channels present in the membrane of DRG neurons can lead to a similar state of hyperexcitability of the primary nociceptive afferent (Devor, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…26 currents. 30,31 The Na V currents were recorded in response to every stimulation potential from -70 to +50 mV in 10 mV increments.…”
Section: Isolation Of Na V Currentsmentioning
confidence: 99%